A Review on Consumption of Raw or Heated Cow Milk (International Journal of Innovative Research in Engineering & Management, 2023)
In the framework of the present  inclination towards greater organic commodities, there  would seem to be an growing desire for bare exploit feasting, since raw milk is linked with many claimed health  advantages that are thought to be lost when heated. Many  human infections, on the other hand, It's possible to  separate it from fresh bovine dairy. Although the  prevalence of gastrointestinal microorganisms in  uncooked cow dairy varies, their existence has been  demonstrated in several investigations, and  gastrointestinal infections produced by Gastroenteritis,  Salmonella., and highly virulent appropriate anti E. coli  have been reported often. In affluent countries, milk-borne  and dairy illnesses accounted for 2e6 % of microbial  poisoning illnesses. This review's goal is to give  methodically volume data on the risks and benefits of  consuming raw and warmed cows dairy. Both  physiological and microbial and nutritional aspects are  taken into account. As a result, raw milk intake is shown  to represent a genuine health risk owing to the possibility  of contamination with human pathogens. As a result, it is  highly advised that milk be heated before drinking.  Heating (especially ultra-high temperature and comparable  treatments) will not significantly affect the nutritional  content of raw milk or other advantages associated with  raw milk intake, with the exception of a changed  organoleptic character.
Keywords: Raw milk; Pathogens; Risk/benefit; Nutrition; Heat treatment